An unusual case of chest pain. (20th February 2013) - Ng, Peter
Abstract : Boerhaave's syndrome is a rare but life-threatening condition characterised by spontaneous rupture of the oesophagus. Owing to its rarity, it is often not thought about as a cause for chest pain and is often admitted under a medical ward. This can lead to a delayed diagnosis with unfavourable outcomes. A 93-year-old female presented with severe atypical chest pain that was difficult to control. Her initial baseline tests were normal but her condition deteriorated and she desaturated through the night. A repeat chest x-ray showed right basal consolidation and pneumomediastinum. A diagnosis of Boerhaave's syndrome was made. She was unfortunately at this stage critically unwell and continued to deteriorate. She died 17 h after admission.